Employability on vocational high school students in the ”3T” area Bawean Island - Tentama, Fatwa; Santosa, Budi; Ali, Raden Muhammad (Journal of Education and Learning (EduLearn), 2024)
Vocational high schools in ”3T” area on Bawean Island have limitations in human resources quality, equipment, production or practice tools, and industrial partnership, which differed from the vocational high schools located in advanced and developed areas. This research objective is to discover the description of employability to the vocational high school students in ”3T” area in Bawean island. The research method applied was the qualitative method using the phenomenology approach. The data collection was obtained through semi-structured interviews. This research participant was eight students at vocational high school "X," "Y," "Z," and "W" schools in Bawean Island, which is one of the ”3T” area. The analysis method in this research was content analysis. This research result shows that students in the ”3T” area were showing their effort to prepare themselves in facing the job market by enhancing their employability in learning activities within the class or practice in the laboratory. The students' employability includes skills, knowledge, comprehension, personality, career identity, social and human relations, and personal adaptability. Students realize that they are in the "3T" area and must work harder to improve their work skills so as not to lose their jobs.